Thermal comfort and energy performance of a dedicated outdoor air system with ceiling fans in hot and humid climate - Mihara, Kuniaki; Sekhar, Chandra; Takemasa, Yuichi; Lasternas, Bertrand; Tham, Kwok Wai (Energy and buildings, 2019)
•Thermal comfort and energy saving potential of DOAS-CF was studied.•Thermal comfort and IAQ acceptability were highest satisfaction at 27 °C at 0.94 m/s.•Mean thermal sensation was highly correlated to the average SET* as a linear function.•Annual energy consumption of DOAS-CF was reduced by 25.8% as temperature rose 3 °C. The performance of a Dedicated Outdoor Air System integrated with ceiling fans (DOAS-CF) to enhance thermal comfort, perceived air quality (PAQ) and energy-saving potential was examined. 26 subjects were exposed to the combinations of temperatures (24, 27 and 30 °C) and air velocities in the range of 0.07 to 1.87 m/s at relative humidity (RH) of 60% for 3.5 h. The results showed that subjects felt thermally neutral and comfortable at 24 °C with air velocity of 0.07 m/s, 27 °C with air velocity of 0.94 m/s and 30 °C with air velocity of 1.87 m/s. Thermal comfort (87%), thermal preference (72%), thermal acceptability (100%) and indoor air quality acceptability (98%) were highest at 27 °C at 0.94 m/s. The mean thermal sensation was highly correlated to the average SET* as a linear function. An energy simulation tool (IES-VE) was used to simulate the energy consumption and quantify the energy savings of the DOAS-CF. Relative to a typical room design condition of 24 °C with a conventional air-conditioning system, DOAS-CF achieved a 25.8% reduction in annual energy consumption when the room temperature was raised by 3 °C but compensated by increased air movement.